Cytochrome B (Cyt B) mtDNA genetic diversity of the second filial (F2) of Banteng Bali cross in UPT-PTHPT Pucak, South Sulawesi Indonesia. Issue 1 (June 2021) - Rahim, L; Bugiwati, S R A; Adhianto, A E; Dagong, M I A; Saking, N; Pasino, S; Arifin, M
Abstract: Bali cattle are native to Indonesia and are the result of domestication from Banteng, ( Bos banteng ). The cytochrome B gene is widely used in systematic studies to solve differences at many taxonomic levels and has been considered as one of the genes used in phylogenetic action. Cytochrome B is also very useful for comparing species in the same genus or the same family. Genetic characterization tests were carried out to identify the characteristics of mtDNA specific identifiers of Bali cattle with Banteng Bali cross (F2). The edited nucleotide sequences are then aligned using the Clustal W program contained in the MEGA 6 software. Construction of the phylogeny tree is carried out using the MEGA 6 program based on p-distance values. Phylogeny tree construction uses bootstrap UPGMA method with 1000 replication. Based on genetic distance analysis, it shows that Bali cattle and Banteng Bali cross (F2) with Bos javanicus have a genetic distance that is relatively the same as the genetic distance value (0.000–0.001) but has a great genetic distance with the Bos taurus, Bos indicus and Bubalus bubalis with genetic distance values ( 0.050–0.094). This shows that in cytochrome B, Bali cattle and Banteng Bali cross F2 have identical genetic distances. Based on the UPGMA tree phylogeny method, the results show that the kinship group 1 (Bali cattle (CBB3 and CBB7), Banteng Bali cross (F2) (CBC1, CBC7, CBC8, and CBC9) with Bos javanicus ) and group 2 (Bali cattle (CBB2, CBB4, CBB8, CBB9) and Banteng Bali cross (F2) CBC10) are in the same branch showing that the results are relatively similar and have a close kinship. It can be concluded that the characteristics of mtDNA cytochrome B in Bali cattle and Banteng Bali cross F2 were relatively the same and both have a very close relationship.